Geography and Empire in Virgil's Georgics. A study of the poem and its reception in Britain and the British Empire, c.1820-1930 - KERRIGAN, CHARLIE (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2018)
This thesis is a history of Virgil?s Georgics, one which combines a reading of the text (Chapter 1) with investigation of its reception in Britain and the British empire (Chapters 2 and 3). It argues that an aesthetic trend is visible in British scholarly discourse on the poem: the Georgics has been characterised as a work of artistic perfection, and, in the process, important political and imperial contexts have been minimised or ignored. Chapter 1 seeks to re-politicize the text by exploring its geography ? the ways in which it represents the many peoples and places from across the orbis terrarum depicted in its lines ? and by suggesting ways in which this geography can inform a more political appreciation of the poem. Chapters 2 and 3 then seek to offer an alternative history to its aesthetically-inclined scholarly reception. By using a broad range of archival material, including contemporary articles from newspapers and periodicals across Britain, these Chapters show the relevance which the poem?s primary, agricultural, subject matter had for a British readership, and how the poem was used to describe peoples and places from around the British empire and the wider world. This global description is often implicated in the rhetoric and practice of imperialism, in ways not unrelated to the Georgics? own depiction of the world.
APPROVED
Keywords: Virgil, classical reception